GAMBARAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA UD CIPTA GUNA KREASI TAHUN 2024 - Mila Marwati; Joko Malis Sunarno (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2024)
PPE (Personal Protective Equipment) is a piece of equipment that must be used when working according to occupational hazards and risks to maintain the safety of the worker himself and the people around him. The risks from work in cutting and drilling are exposure to dust and exposure to the machine. The purpose of this study is to find out the overview of knowledge, compliance and existence of PPE at UD Cipta Guna Kreasi. This study is a descriptive research using the cross sectional method. The respondents in this study were 30 employees in part of cutting, drilling, sorting, weaving and packaging at UD Cipta Guna Kreasi. The observed variables are employee characteristics, knowledge and compliance in using PPE. The data used in this study are primary data obtained from observations, interviews, questionnaires, checklists and secondary data. The results of the study were the availability of PPE only (14.3%), Employees' knowledge about PPE was mostly in the good category, namely (50.0%). The level of compliance is in the section of the compliance level (12.5%), for the compliant drilling part (22.2%), in the sorting section (25.0%) and in the weaving and packaging section (20.0%). The conclusion in this study is that compliance with the use of PPE is still low due to the low level of education, which is the most elementary school graduates (40.0%), and the availability of PPE also affects the absence of complete and standard PPE. Suggestions for UD Cipta Guna Kreasi must provide complete PPE that meets SNI standards.